Comparison of Endoflas and Zinc oxide Eugenol as root canal filling materials in primary dentition - Nivedita Rewal; Arun Singh Thakur; Vinod Sachdev; Nanika Mahajan (Wolters Kluwer Medknow Publications, 2014)
Background: Zinc oxide eugenol has long been the material of choice of pediatric dentists worldwide, although it fails to meet the ideal requirements of root canal filling material for primary teeth. Endoflas, a mixture of zinc oxide eugenol, calcium hydroxide, and iodoform, can be considered to be an effective root canal filling material in primary teeth as compared with zinc oxide eugenol. This study was carried out to compare zinc oxide eugenol with endoflas for pulpectomy in primary dentition. Aim: The objective of the study was to compare clinically and radiographically success rates of zinc oxide eugenol with endoflas for the root canal filling of primary teeth at 3, 6, and 9 months. Design: Fifty primary molars were included in the study with 26 teeth in Group I (Endoflas) and 24 in Group II (zinc oxide eugenol). A single visit pulpectomy was carried out. Results: The overall success rate of zinc oxide eugenol was 83% whereas 100% success was found in the case of endoflas. The obtained results were compiled and subjected to statistical analysis using the chi-square test. The difference in the success rate between the two was statistically significant (P < 0.05). Conclusion: Endoflas has shown to have better results than zinc oxide eugenol. It should therefore be the material of choice for root canal treatment in deciduous dentition.